Pathophysiological aspects of ischemic stroke: a narrative review (Research, Society and Development, 2023)
Ischemic stroke is characterized by the World Health Organization (WHO) by a set of factors: abrupt development of focal signs, in reversible or global cases, the dysfunction must last for more than 24 hours (less than that, this is a transient ischemic attack). Given the epidemiological importance of stroke, this article aims to discuss the pathophysiological mechanisms of the disease. This study is a narrative review with the purpose of discussing and describing stroke and its pathophysiology, as well as demonstrating how this syndrome affects the personal lives of affected individuals. The following databases were used: SciElo (Scientific Electronic Library Online) and PubMed (US National Library of Medicine), with scientific data from December 2, 2022, with no language restriction and no restriction on the year of publication. As the nervous system commands the main functions of the human body, it needs oxygen in abundance and for this to occur, it has a large-scale circulatory system through the arterial branches, which supply blood. Those that originate from the corticality and the basal nuclei extend into a myriad of capillaries that interpose and anastomose successively, ensuring a complete collateral circulation. Anatomically, they are not terminal arteries and, functionally, they are close (in the sense that they allow infarcts) when other risk factors are placed before them. In short, the pathophysiology of stroke establishes a great relationship between the arteries suffered by the infarction and the clinical picture of the patient affected by the disease.